2014
DOI: 10.1108/ijse-05-2013-0120
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Turkish students against markets: does studying economics matter?

Abstract: Purpose -The literature shows economics students to be more market oriented than students from other disciplines. A major shortcoming of this work, however, is that it is based on research carried out in the west. The purpose of this paper is to examine the attitudes of Turkish economics students' towards markets. Design/methodology/approach -The study reported here uses a survey developed by Lephard and Breeden to investigate students' attitudes towards markets. The survey consists of 11 market-positive state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Whaples [31] found a small shift towards a belief that 'markets are fair' during the course of economics students' first year of study. However, Cokgezen and Cilingirturk [12] found that these results were not replicated with their sample of Turkish undergraduates in Istanbul. We found one previous study that investigated the association between undergraduates' economic beliefs and their attitudes towards environmental policies.…”
Section: The Effect Of Studying Economics On Attitudes Towards the Romentioning
confidence: 80%
See 1 more Smart Citation
“…Whaples [31] found a small shift towards a belief that 'markets are fair' during the course of economics students' first year of study. However, Cokgezen and Cilingirturk [12] found that these results were not replicated with their sample of Turkish undergraduates in Istanbul. We found one previous study that investigated the association between undergraduates' economic beliefs and their attitudes towards environmental policies.…”
Section: The Effect Of Studying Economics On Attitudes Towards the Romentioning
confidence: 80%
“…Some other studies [10][11][12] have made a priori judgements that individuals will adopt different stances towards the role of the government, according to the context (e.g., welfare, environment, health). For example, Lephardt and Breeden [13] include one item: "in my opinion the market system in the US encourages abuse of the environment".…”
Section: General Attitudes Towards Markets and Government In The Economymentioning
confidence: 99%
“…For instance, Price and Wolfers’ (2010) study on racial bias among basketball referees could have incorporated a (second-order) analysis of how the publication of this first-order theory can lead to new regulations, different training of umpires, and just generally an awareness of racial bias—changes that could lead to an adjustment of behavior and explain the self-falsification of their own original study in this particular setting. In the case of the argued change in self-interested behavior among economics students, one could identify whether it is the syllabus used, the teachers’ beliefs, or other elements that influence behavior (Cokgezen and Cilingirturk 2014). Even if one rejects the existence of self-fulfillment, but “merely” accepts simple, generic performativity, one acknowledges that (the adoption of) theories can influence social behavior, and to properly assess theories and the impact adoption might have, one should actually carry out such comparative, social science experiments, as pointed out by Santos (2011).…”
Section: A Realistic Social Science Realism: Cooling the Firementioning
confidence: 99%